Comparative Characteristics of the Incidence of Healthcare-Associated Infections in the Chelyabinsk region and in the Russian Federation in Total - O. A. Orlova (Эпидемиология и вакцинопрофилактика, 2015)
Currently, the problem of prevention and treatment of healthcare-associated infections (HAI), only in hospitals from 5 to 20% of patients HAI get sick. In Chelyabinsk region, in comparison with the Russian Federation, the quantity of the infections connected with delivery of health care tends to growth. The greatest number of HAI is registered in hospitals of a surgical profile 70.3 ± 5.7% (in the Russian Federation - 31.4 ± 0.2%). In area hospital-acquired pneumonia steadily holds the first - second place in structure of HAI (38.2 ± 10.3%) in the country - the fourth - fifth (10.1 ± 5.1%). Detection of distinctions in structure of HAI in Chelyabinsk region and in the country in general demand further studying for the purpose of identification and introduction of the most effective preventive and antiepidemic actions.